The effect of kahoot application towards students’ reading comprehension at the Eleventh Grade of SMAN 1 Cijaku Lebak Banten in Academic Year 2023/2024 - Adawiah, Siti Robeah; Rohimajaya, Nur Azmi; Riandi (CV. Kurnia Grup, 2024)
This research paper aims to investigate the effect of kahoot Application towards students’ Reading Comprehension at the Eleventh Grade of SMAN 1 Cijaku Lebak Banten in Academic Year 2023/2024. The method used in this research was quantitative method. The design of this research was quasi-experimental design and cluster random sampling: the researcher has chosen two classes are a control class and an experimental class. The technique in choosing the sample is cluster random sampling; the researcher used XI IPS 1 (31 students) as class control and XI IPA 2 (36 students) as class experimental. The experimental group was taught recount text in Reading comprehension used kahoot application, whereas the control group was taught used wordwall. In analyzing the data, the researcher used Independent sample t-test by SPSS 25.0 statistical computation to analyze the hypotheses test. The researcher has found the result t-count (1.727) and Significant two-tailed = 0.044 < α 0.05. From these data could be interpreted that there is a significant difference between the two groups in obtaining scores, because the result is a significance value of less than 0.05, which means Ha is accepted. According to the criteria of the test, it could be concluded that there was progress in the effect of kahoot Application towards students’ Reading Comprehension at the Eleventh Grade of SMAN 1 Cijaku Lebak Banten.